2005
DOI: 10.1188/05.onf.633-640
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue, Psychological Distress, Coping Resources, and Functional Status During Radiotherapy for Uterine Cancer

Abstract: Nurses must inform patients receiving radiotherapy about the expected changes in fatigue and functional status. Pretreatment screening for fatigue is needed to identify patients at risk for developing fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
66
1
9

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 49 publications
4
66
1
9
Order By: Relevance
“…In their study of fatigue, psychological distress, and functional status among women receiving radiotherapy for uterine cancer, Ahlberg and coworkers found highly statistically significant negative correlations between general fatigue and multiple domains of QoL, including physical, role, emotional, cognitive, and social functioning (all p < .001, except social functioning p = .002) [36]. They further demonstrated that physical, role, and cognitive functioning remained highly negatively correlated with general fatigue over time.…”
Section: Thementioning
confidence: 95%
See 2 more Smart Citations
“…In their study of fatigue, psychological distress, and functional status among women receiving radiotherapy for uterine cancer, Ahlberg and coworkers found highly statistically significant negative correlations between general fatigue and multiple domains of QoL, including physical, role, emotional, cognitive, and social functioning (all p < .001, except social functioning p = .002) [36]. They further demonstrated that physical, role, and cognitive functioning remained highly negatively correlated with general fatigue over time.…”
Section: Thementioning
confidence: 95%
“…In general, however, the severity of CRF following chemotherapy peaks within 4 or 5 days of completion of treatment and gradually lessens over time, although it never recedes to pretreatment levels [30,35]. CRF is reported in around 80% of patients undergoing radiotherapy, and a number of studies have found that the severity of the fatigue experienced by such patients gradually increases over the course of treatment [20,[36][37][38]. In a detailed study of the incidence and severity of side effects during the course of radiation therapy, fatigue was the most prevalent and the most severe symptom reported by patients (Fig.…”
Section: The Fatigue Reported By Patients With Cancer Is Severementioning
confidence: 99%
See 1 more Smart Citation
“…It shows that, according to the disease stage, the associated factors may vary. It seems that, in outpatients, the predictors include a reasonable amount of socio-demographic variables (female gender, high education, having a regular job and living without a partner), besides depression and performance status (10)(11)(12) . On the other hand, fatigueassociated factors in patients with advanced cancer are basically related to other signs and symptoms present in terminally ill patients (e.g.…”
mentioning
confidence: 99%
“…Mallinson et al[17] beschrieben eine inverse Korrelation zwischen selbstberichteter Erschöpfung und physischer Funktionsfähigkeit. Ahlberg et al[1] fanden signifikante negative Korrelationen zwischen tumorbedingter Fatigue und zahlreichen Bereichen der Lebensqualität, einschließlich der physischen, emotionalen, kognitiven und sozialen Funktionsbereiche. Eine Einschränkung ihrer Lebensqualität wird von vielen Patienten über alle Krebsarten hinweg genannt[1].…”
unclassified